2015
DOI: 10.1097/qai.0000000000000512
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexual Partners of Male People Who Inject Drugs in Vietnam Have Poor Knowledge of Their Male Partners' HIV Status

Abstract: SP interventions reached HIV-negative women in serodiscordant relationships, and some improvements occurred in condom use and relationship characteristics. Nevertheless, our findings suggest that at least 11,000 SPs in Vietnam may be at high risk for HIV infection because of incorrect knowledge of their partners' HIV status. Interventions should be strengthened in HIV testing, disclosure, and treatment, as well as empowerment of SPs as individuals, within couples, and as communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Compared to men, women had less advanced disease, with higher CD4 cell counts and fewer complications, probably because women were mostly tested because of their husband’s illness (Table 1 ). Testing of sexual partners of PWID is important in this setting; a cross-sectional study in a similar setting showed that this particular subgroup have a very high HIV risk [ 33 ]. Screening of women in antenatal care is not routinely done in Indonesia; indeed only one out of the 43 pregnant women in this cohort was referred from an obstetric care.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to men, women had less advanced disease, with higher CD4 cell counts and fewer complications, probably because women were mostly tested because of their husband’s illness (Table 1 ). Testing of sexual partners of PWID is important in this setting; a cross-sectional study in a similar setting showed that this particular subgroup have a very high HIV risk [ 33 ]. Screening of women in antenatal care is not routinely done in Indonesia; indeed only one out of the 43 pregnant women in this cohort was referred from an obstetric care.…”
Section: Discussionmentioning
confidence: 99%
“…21 A study of 403 female IDUs found that only 50% of women in Hanoi and 63% in Ho Chi Minh City had ever heard of NSPs 22 , and only 17% and 24% in each city, respectively, had received a free needle in the last 6 months. 22 …”
Section: Country Case Studiesmentioning
confidence: 99%
“…For PWID in Vietnam, low levels of education may serve as a barrier for HIV and substance use treatment . We believe the limited number of females in Indonesia and Vietnam accurately reflects the population of PWID in these countries based on culture and historic precedence . The gender distribution in Ukraine is similar to the distribution in Russia and the Baltic States .…”
Section: Discussionmentioning
confidence: 85%